2018
DOI: 10.1001/journalofethics.2018.20.6.org1-1806
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Improve Detection of Nonaccidental Pediatric Burns

Abstract: Our multidisciplinary method might provide a more consistent and reliable method for identifying cases of suspected abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A recent mapping review suggested that health and social care services aiming to improve awareness of safeguarding issues may benefit from service development interventions that go beyond high‐quality training provision (Chambers et al, 2021). Another recent study found that the implementation of a multidisciplinary model whereby all paediatric burns were evaluated by an internal child protection team may provide a more consistent and reliable method of identifying abuse cases (Nigro et al, 2018). SWs and HVs would benefit from further training in the clinical features of abusive and neglectful burns.…”
Section: Discussionmentioning
confidence: 99%
“…A recent mapping review suggested that health and social care services aiming to improve awareness of safeguarding issues may benefit from service development interventions that go beyond high‐quality training provision (Chambers et al, 2021). Another recent study found that the implementation of a multidisciplinary model whereby all paediatric burns were evaluated by an internal child protection team may provide a more consistent and reliable method of identifying abuse cases (Nigro et al, 2018). SWs and HVs would benefit from further training in the clinical features of abusive and neglectful burns.…”
Section: Discussionmentioning
confidence: 99%